Job creation patterns in the Malaysian manufacturing sector: does technology matter? - Samsi, Aznita; Samsuddin, Siti Nur Fatihah; Abdullah, Norehan; Maamor, Selamah; Abdullah, Hussin; Nayan, Sabri (IJTech, 2018)
The Malaysian government claims that the implementation of advanced technology in the production process following the Economic Transformation Program (ETP) will create many jobs in the economy. To evaluate this statement, this study calculates the rate of job creation based on the formula developed by Davis and Haltiwanger (1999), plotting and analysing the pattern of job creation in high- and low- technology level sub-sector groups. From the descriptive analysis, both technology groups show distinctive patterns of job creation. Hence, this study provides information to policymakers to enable them to strike a balance between technology and job creation capacity in the manufacturing sector.